Marketisation and the public good: a typology of responses among museum professionals - Aroles, Jeremy; Morrell, Kevin (SAGE Publications, 2025)
Across Western democracies, the public sector has undergone significant changes following successive waves of marketisation. Such changes find material expression in an organisation’s logic and associated vocabulary. While marketisation may be adopted, a growing body of research explains how it is often resisted as public sector professionals reject its logic and vocabulary. We contribute to this debate by detailing additional, theoretically important responses. Rather than simply rejecting or adopting both the logic and vocabulary of marketisation, this article shows how UK museum professionals decouple these. Our analysis shows how museum professionals either fashion generic market vocabulary (e.g. customer, value) to pursue local projects or sustain terms such as public and culture to cling to longer-standing ideals of publicness. Partly because of the nature of cultural goods, we propose the museum sector as a paradigm case to illustrate this phenomenon, but our argument has broader implications for the public sphere.
Keywords: culture; decoupling; marketisation; museums